Professional identity in physical education: a review of literature - Catarina Amorim; Elsa Maria Ribeiro-Silva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Teachers’ professional identity shapes teachers’ educational views, impacting their behaviour, action and decision making. This study was designed with the goal of locating, compiling and analysing articles regarding professional identity in the physical education context and identifying elements that contribute to professional identity construction. We selected professional identity and physical education as search items in Web of Science, ERIC, SPORTDiscuss and Scopus. To investigate the previous decade of research, we limited the study to articles published between 2010 and 2020. This work combines recent publications written in Portuguese, English and Spanish. The database search yielded 27 relevant articles. The themes present in the articles can be divided into two groups: those linked to key actors and influences on physical education teachers’ professional identity, and those related to physical education preservice teachers. The following themes were discovered to influence teachers’ professional identity formation: relationships (established within their acting context), identity negotiation, identity transformation, lifelong learning, peer perception and the class context. The following themes impact preservice teachers’ professional identity formation: teaching practicum experience, prior experiences, a community of practice and the teachers’ body. Professional identity formation is an intricate process characterised by a diverse mix of personal, professional, environmental and social representations that interact in real time.